Exposing misclassified HIV/AIDS deaths in South Africa - Jeanette Kurian Birnbaum; Christopher JL Murray; Rafael Lozano (The World Health Organization, 2011)
OBJECTIVE: To quantify the deaths from human immunodeficiency virus (HIV) infection or acquired immunodeficiency syndrome (AIDS) that are misattributed to other causes in South Africa's death registration data and to adjust for this bias. METHODS: Deaths in the World Health Organization's mortality database were distributed among 48 mutually exclusive causes. For each cause, age- and sex-specific global death rates were compared with the average rate among people aged 65-69, 70-74 and 75-79 years to generate "relative" global death rates. Relative rates were also computed for South Africa alone. Differences between global and South African relative death rates were used to identify the causes to which deaths from HIV/AIDS were misattributed in South Africa and quantify the HIV/AIDS deaths misattributed to each. These deaths were then reattributed to HIV/AIDS. FINDINGS: In South Africa, deaths from HIV/AIDS are often misclassified as being caused by 14 other conditions. Whereas in 1996-2006 deaths attributed to HIV/AIDS accounted for 2.0-2.5% of all registered deaths in South Africa, our analysis shows that the true cause-specific mortality fraction rose from 19% (uncertainty range: 7-28%) to 48% (uncertainty range: 38-50%) over that period. More than 90% of HIV/AIDS deaths were found to have been misattributed to other causes during 1996-2006. CONCLUSION: Adjusting for cause of death misclassification, a simple procedure that can be carried out in any country, can improve death registration data and provide empirical estimates of HIV/AIDS deaths that may be useful in assessing estimates from demographic models.